Theoretical interpretation of scanning probe microscopy images involving organic molecules - Lakin, Andrew J. (2014)
Scanning probe microscopy allows the investigation and manipulation of matter at the atomic and molecular level, and is crucial in the development of new and novel techniques within nanoscience. However, to understand the information obtained from the various forms of scanning probe microscopy, a thorough theoretical understanding is necessary. Often this theoretical background is provided through density functional theory, which, while incredibly powerful, has limitations with regards to the size and complexity of the systems in which it can investigate. Thus, for more complicated systems, alternative techniques are desirable to be used both independently and alongside density functional theory. In this work, theoretical techniques are constructed that allow the information obtained from both scanning tunnelling microscopy and atomic force microscopy to be investigated for a variety of systems. These techniques are all based around Huckel molecular orbital theory or extended Huckel molecular orbital theory, and use a simple linear combination of atomic orbital basis, that allows rapid analysis of various systems. The main focus of the work is the scanning probe microscopy of the C60 fullerene molecule. Theoretical scanning tunnelling microscopy images are constructed for the cases where C60 is adsorbed on both the substrate and the scanning probe in the form of a functionalised tip, as well as when a tip-adsorbed molecule interacts with a sample-adsorbed molecule. The atomic force microscopy images of surface adsorbed C60 are considered, with the main focus centred on the repulsive interaction observed due to the Pauli exclusion principle. The structure of the scanning probe, and the effect this has on this imaging is examined, as well as considering the atomic force microscopy images obtained when two C60s interact. Molecules other than C60 are also considered, with the techniques developed used to interpret and understand the atomic force microscopy images obtained when a pentacene and a PTCDA molecule interact with a carbon monoxide functionalised tip. The theoretical work is accompanied throughout by a variety of experimental work, both from previously published work, and from unpublished work obtained by the University of Nottingham nanoscience group. Much focus is given to the interaction between C60 and the Si(111)-(7x7) reconstruction, both in the sense of a functionalised tip interacting with the surface, and with the interactions present where a C60 is adsorbed onto a surface. In doing so, previously postulated bonding sites for C60 on this surface have been verified.